Investigating requirement engineering techniques in the context of small and medium software enterprises - Besrour, S. (Institute of Electrical and Electronics Engineers Inc., 2016)
Numerous requirement techniques have been proposed in the last decade in order to reduce requirement engineering challenges. However, Large number of requirement engineering techniques causes confusion while technique selection process. Thus, there is a need to investigate requirement techniques. To address this objective, techniques have been studied in the last two decade between the years 1995 and 2016 using systematic literature review (SLR) to explore other studies findings and results. A total of 15 techniques has been specified in the context of requirement engineering. Additionally, identified techniques have been further investigated using quantitative study through small and medium software enterprises. Where a total of 250 surveys have been collected, after eliminating incomplete surveys 217 completed surveys used for data analysis. Concluding results show that out of 15 techniques, 12 techniques have been rated as supported. Lastly identified techniques aim to benefit software enterprises particularly new enterprises to have a better understanding about techniques support level in the context of requirement engineering. Â© 2016 IEEE.